Perbandingan Target dan Realisasi Penerimaan Pajak Penghasilan Orang Pribadi di KPP Pratama Makassar Barat Selama Periode 2019-2023 - Wiwin Riski Windarsari; Adriansyah, Adriansyah; Ridha, Achmad; Zaimar, Fina Ruzika; Haruna, Hasisa (Indonesian Journal Publisher, 2025)
This study examines the comparison between tax revenue targets and the realization of individual income tax receipts at KPP Pratama Makassar Barat from 2019 to 2023. It also identifies the factors contributing to discrepancies between targets and actual revenue and proposes policies to improve taxpayer compliance. A descriptive quantitative approach is used with secondary data obtained from KPP Pratama Makassar Barat's official reports. The data includes tax revenue targets, actual individual income tax collections, and taxpayer compliance levels. Data collection is conducted through document analysis, while comparative and trend analysis are applied to identify gaps and patterns over the study period. The findings show fluctuations in tax revenue achievement. In 2019 and 2020, realization exceeded 140% of the target, reflecting high compliance. However, in 2021, revenue dropped to 70.95% due to the COVID-19 pandemic. By 2022 and 2023, realization improved to 95.71% and 103.02%, indicating economic recovery and enhanced compliance measures. Discrepancies in tax revenue targets and realization are influenced by macroeconomic conditions, compliance levels, and policy effectiveness. To enhance compliance, tax education, stricter supervision, incentives, and better reporting systems are recommended. These measures can ensure sustainable revenue growth and improved taxpayer compliance.